2021
DOI: 10.1038/s41598-020-80478-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic exercise training on muscle plasticity in a mouse model of cervical spinal cord injury

Abstract: Cervical spinal cord injury (SCI) results in permanent life-altering motor and respiratory deficits. Other than mechanical ventilation for respiratory insufficiency secondary to cervical SCI, effective treatments are lacking and the development of animal models to explore new therapeutic strategies are needed. The aim of this work was to demonstrate the feasibility of using a mouse model of partial cervical spinal hemisection at the second cervical metameric segment (C2) to investigate the impact of 6 weeks tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Exercise training is reported to improve the oxidative capacity of skeletal muscles in rodents (Egan & Zierath, 2013). However, there was no pronounced phenotypic shift of muscle fibres in response to chronic exercise training in previous studies (Ishihara et al, 1998;Jesus et al, 2021;Kriketos et al, 1995;Rodnick et al, 1992). The results of the present study (Figs 5 and 7) showed no effects of exercise training on the fibre phenotype in the DMSO-treated group, which is consistent with previous observations.…”
Section: Role Of H3k27me3 In Adaptation To Exercisesupporting
confidence: 92%
“…Exercise training is reported to improve the oxidative capacity of skeletal muscles in rodents (Egan & Zierath, 2013). However, there was no pronounced phenotypic shift of muscle fibres in response to chronic exercise training in previous studies (Ishihara et al, 1998;Jesus et al, 2021;Kriketos et al, 1995;Rodnick et al, 1992). The results of the present study (Figs 5 and 7) showed no effects of exercise training on the fibre phenotype in the DMSO-treated group, which is consistent with previous observations.…”
Section: Role Of H3k27me3 In Adaptation To Exercisesupporting
confidence: 92%
“…Thus, tasks training fine digit control (e.g., SPRG) may result more appropriate for the recovery from mild or moderate injuries, or those affecting distal rather than proximal movements. On the other hand, treadmill locomotion ( 48 ) and forced/voluntary running wheel ( 49 ), which involve strength/cardiovascular resistance, can also promote recovery of forelimb movements. However, these trainings may entail a confounding factor when interpreting motor improvement as it is difficult to dissect the neural bases from the exercise-induced benefits ( 31 ).…”
Section: Rehabilitative Training: An Engine For Neuroplasticitymentioning
confidence: 99%
“…Maximum heart rate refers to the highest level of heart rate that can be reached under the maximum load intensity of exercise, reaching the limit of oxygen consumption and heart rate. For example, during exercise, with the increase of exercise load, oxygen consumption and heart rate will also increase [10].…”
Section: Analysis and Discussionmentioning
confidence: 99%